Dynamic linking and personalization on web. - Sah, M; Hall, W; Roure, D (ACM, 2010)
Web browsing is a complex activity and users need to be supported with additional guidance. In our research, we developed a novel Semantic Web browser, which is called SemWeB, in order to assist Web browsing using linked data and Adaptive Hypermedia (AH). SemWeB is an extension to the Mozilla Firefox Web browser. SemWeB adds a semantic layer to Web documents: it annotates Web pages using a linked data domain (i.e. DBpedia) and creates context-based hyperlinks on Web pages to guide users to relevant pages. In addition, the information presented to the user is personalized based on a novel behavior based user model. We evaluated our approach on DBpedia, DBLP and ECS (University of Southampton) linked data domains. Our study showed that SemWeB provides a new way of supporting dynamic linking and personalization on Web documents using different linked data domains. © 2010 ACM.